CoA synthase plays a critical role in neurodevelopment and neurodegeneration - Cavestro, Chiara; D’Amato, Marco; Colombo, Maria Nicol; Cascone, Floriana; Moro, Andrea Stefano; Levi, Sonia; Tiranti, Valeria; Di Meo, Ivano (Frontiers in Cellular Neuroscience, 2024)
Background: Coenzyme A (CoA), which is widely distributed and vital for cellular metabolism, is a critical molecule essential in both synthesizing and breaking down key energy sources in the body. Inborn errors of metabolism in the cellular de novo biosynthetic pathway of CoA have been linked to human genetic disorders, emphasizing the importance of this pathway. The COASY gene encodes the bifunctional enzyme CoA synthase, which catalyzes the last two reactions of the CoA biosynthetic pathway and serves as one of the rate-limiting components of the pathway. Recessive variants of this gene cause an exceptionally rare and devastating disease called COASY protein-associated neurodegeneration (CoPAN) while complete loss-of-function variants in COASY have been identified in fetuses/neonates with Pontocerebellar Hypoplasia type 12 (PCH 12). Understanding why the different symptoms emerge in these disorders and what determines the development of one syndrome over the other is still not achieved. To shed light on the pathogenesis, we generated a new conditional animal model in which Coasy was deleted under the control of the human GFAP promoter. We used this mouse model to investigate how defects in the CoA biosynthetic pathway affect brain development. This model showed a broad spectrum of severity of the in vivo phenotype, ranging from very short survival (less than 2 weeks) to normal life expectancy in some animals. Surviving mice displayed a behavioral phenotype with sensorimotor defects. Ex vivo histological analysis revealed variable but consistent cerebral and cerebellar cortical hypoplasia, in parallel with a broad astrocytic hyper-proliferation in the cerebral cortex. In addition, primary astrocytes derived from this model exhibited lipid peroxidation, iron dyshomeostasis, and impaired mitochondrial respiration. Notably, Coasy ablation in radial glia and astrocytic lineage triggers abnormal neuronal development and chronic neuroinflammation, offering new insights into disease mechanisms.